MENINGKATKAN KOMPETENSI SOSIAL DAN KEPRIBADIAN GURU MELALUI PROGRAM PENGAJIAN DI SEKOLAH, KENAPA TIDAK? - Mustaqim, Mujahidil (EDUTECH, 2018)
Abstract. This article would like to address a number of issues that indicate the need for increased social competence and teacher personality as the spearhead of education managers in the field. However, this enormous role is not matched by a mature debriefing of these two compe-tencies for the preparation of a professional teacher candidate. Of the 163 SKSs studied, only 26 credits were granted to form social competence and personality. Means only 16% of the propor-tion of courses for these two competencies. So on this, it needs an independent but planned effort to improve the social competence and personality of teachers, such as through pengajian pro-grams for teachers in schools. This article is formulated by using the reseacrh library approach. There are two main subjects that are studied first, the analysis of the needs of the study program on improving social competence and teacher personality. Second, the objective formulation and content of the study program on improving the social competence and teacher's personality.Â Abstract. This article would like to address a number of issues that indicate the need for increased social competence and teacher personality as the spearhead of education managers in the field. However, this enormous role is not matched by a mature debriefing of these two compe-tencies for the preparation of a professional teacher candidate. Of the 163 SKSs studied, only 26 credits were granted to form social competence and personality. Means only 16% of the propor-tion of courses for these two competencies. So on this, it needs an independent but planned effort to improve the social competence and personality of teachers, such as through pengajian pro-grams for teachers in schools. This article is formulated by using the reseacrh library approach. There are two main subjects that are studied first, the analysis of the needs of the study program on improving social competence and teacher personality. Second, the objective formulation and content of the study program on improving the social competence and teacher's personality.